Anemia in Lymphoma Patients in Indonesia: The Prevalence and Predictive Factors - Hardianti, Mardiah Suci; Rizki, Salsabilla Hasna Mutiara; Arkananda, Hafidz; Dhyanti, Amira L.; Setiawan, Syahru Agung; -, Indrawati; Dinantia, Nugira; Anggorowati, Nungki (Asian Pacific Journal of Cancer Biology, 2021)
Background: The burden of lymphoma is intensified with the presence of anemia. The type of anemia in lymphoma is predominantly anemia of chronic disease. Severe anemia is also often associated with advanced stages leading to poor prognosis and survival as well as a worse quality of life. Objective: In this study, we aimed to observe the incidence of anemia in lymphoma and to identify any associated clinical and laboratory factors. Methods: Data from lymphoma patients admitted between 2012 to 2018 with complete hemoglobin (Hb) levels were collected from the medical records in Dr. Sardjito Hospital, Yogyakarta, Indonesia. Clinical and laboratory parameters included were age, sex, nutritional status, Ann Arbor staging, extranodal involvement, number of extranodal sites, Lactate Dehydrogenase (LDH) level, Eastern Cooperative Oncology Group (ECOG) performance status, platelet count, absolute lymphocyte count (ALC), white blood cell count (WBC), and lymphoma prognostic score (Non-Hodgkin Lymphoma/NHL using Index Prognostic International (IPI), Hodgkin’s Lymphoma/HL using International Prognostic Score (IPS)). Statistical analysis was done to observe the difference in any parameters between patients with anemia and non-anemia. Logistic regression was employed to model the relationship between associated or predictive factors and anemia incidence. Results: Six hundred eleven (611) lymphoma patients were involved in this study, 296 (48.5%) had anemia and 314 (51.5%) did not. Anemia was more prevalent in HL (17/ 33 cases or 51.5%) than in NHL (272/ 564 cases or 48.1%). Patients with anemia frequently presented with mild anemia in 142 (48%), followed by moderate anemia in 139 (46.9%). The incidence of anemia were significantly associated with male sex, advanced Ann Arbor stage (III-IV), underweight, elevated LDH level, abnormal platelet, absolute lymphocyte counts less than 600/mm3, elevated WBC count more than 15,000/mm3, and high total prognostic score (>3). Multivariate analysis demonstrated low or elevated platelet (P=0.044; 95% CI=1.03-8.09) as an independent predictor, meanwhile lymphocytopenia as protective factor (OR=0.05; 95% CI=0.00-0.54; P=0.013). Conclusion: Anemia commonly occurs in Indonesian lymphoma patients. There is an association and increased risk to develop anemia in male, Ann Arbor stage III-IV, underweight, elevated LDH, abnormal platelet, leukocytosis, and high total prognostic score. Abnormal platelet was an independent predictive factor, and lymphocytopenia is one of the protective factor.